Encountering Development in the Age of Global Capitalism : A Case Study - Tang, Kin-Ling (Springer Singapore : Imprint: Springer, 2017)
This book proposes an alternative approach to understanding development and discusses the possibilities of alternative development in the age of global capitalism from a socio-cultural perspective. Tracing the development of Mui Wo, a rural town on the outskirts of Hong Kong, for more than a decade, it explores the factors that have allowed it to stand apart from the metropolis and follow a path of development that is distinct from the rest of Hong Kong. It also discusses how a place and its people, with their own time-space conceptions, respond to the changes prompted by the exigencies of global capitalism. The book goes beyond institutional concerns and focuses on the daily life of ordinary people. It identifies the forces underlying globalisation, addresses what happens when such forces interact with local ones, and explores the resultant diversions and diversifications. The book is an invitation to all those who are interested in reflecting on heterogeneity and diversity amidst the impulses of globalisation.
Keywords: Social sciences.; Environmental geography.; Development economics.; Cultural studies.; elektronické knihy; electronic books